Effects of Sglt2 Inhibitors on The Heart - ABDELBAKI, M.; Baghous, H. (Clinical Medicine And Health Research Journal, 2023)
Cardiovascular disease and type 2 diabetes are prevalent throughout the world and represent a real public health problem. The prevalence of T2DM ranges from 6.9% to 10.2% in developed countries and more than 7% in developing countries.